Analysis of a Human cDNA Containing a Tissue-Specific Alternatively Spliced LIM Domain - Putilina, T.; Jaworski, C.; Gentleman, S.; McDonald, B.; Kadiri, M.; Wong, P. (Biochemical and biophysical research communications, 1998)
A unique clone, isolated from a human pancreatic cDNA library, was sequenced and characterized. Northern blot analysis showed that the gene is active in a number of fetal and adult tissues, and immunoblots showed expression in nuclear and cytosolic cell fractions. The gene corresponding to the clone was localized to chromosome 13 by human/rodent somatic cell hybrid panels. The largest open reading frame contains a LIM domain, and the deduced peptide from the open reading frame appears to have the characteristics of a LIM-only protein, designatedLMO7.RT-PCR and genomic sequence analyses indicate that expression of this gene product is subject to tissue-specific modulation by elimination of the LIM domain by alternative splicing in neural tissues.